A Simple Aerial Photogrammetric Mapping System Overview and Image Acquisition Using Unmanned Aerial Vehicles (UAVs) - Wenang Anurogo; Muhammad Zainuddin Lubis; Hanah Khoirunnisa; Daniel Sutopo Pamungkas; Aditya Hanafi; Fajar Rizki; Ganda Surya; Arini Dewi Lestari Situmorang; Dirgan Timbang; Perdi Novanto Sihombing; Catur Agus Lukitasari; Novita Ayu Dewanti (Politeknik Negeri Batam, 2017)
Aerial photogrammetry is one of the Alternative technologies for more detailed data, real time, fast and cheaper. Nowadays, many photogrammetric mapping methods have used UAV / unmanned drones or drones to retrieve and record data from an object in the earth. The application of drones in the field of geospatial science today is in great demand because of its relatively easy operation and relatively affordable cost compared to satellite systems especially high - resolution satellite imagery. This research aims to determine the stage or overview of data retrieval process with DJI Phantom 4 (multi - rotor quad - copter drone) with processing using third party software. This research also produces 2 - dimensional high resolution image data on the research area. Utilization of third party software (Agisoft PhotoScan) making it easier to acquire and process aerial photogrammetric data. The results of aerial photogrammetric recording with a flying altitude of 70 meters obtained high resolution images with a spatial resolution of 2 inches / pixels.